Pengaruh Kecukupan Modal dan Penyaluran Kredit Pada Profitabilitas Dengan Risiko Kredit Sebagai Pemoderasi - Udayani, Sinta Arya; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
The purpose of this study is to find out and obtain empirical evidence about the effect of capital adequacy and lending on profitability with credit risk as moderating. This research was conducted at the Foreign Exchange National Private Commercial Bank listed on the Indonesia Stock Exchange in 2013-2017. Samples taken were 17 companies with a total sample of 85 research observations in 5 years, through non-probability methods with purposive sampling technique. The method of data collection in this study is the documentation method. The data analysis technique used is Moderated Regression Analysis. Based on the results of the analysis it is known that banks that have a high level of capital adequacy but if they have a high level of credit risk will reduce profitability and banks that have a high level of credit distribution but if they have a high level of credit risk will reduce bank profitability. Keywords : Capital adequacy, credit distribution, credit risk, profitability